SISTEM INFORMASI PENDAFTARAN SISWA BARU SECARA ONLINE BERBASIS WEB PADA PONPES MODERN RIYADHUL AMIEN - Purnama, Fery (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
Ponpes Modern Riyadhul Amien Desa Dano Lamo Kabupaten Maro Sebo has become a large boarding school. Given the many obstacles that make people less aware about this boarding and registration are still manual, it is necessary for a New Student Registration Information System Online Web Based aiming to expand beyond recognition by the community and improve the quality of their boarding schools in order to be better again. This information system using web-based programming language and MySQL database. The new information system is able to deliver the information to better serve new student enrollment and efficiently.